(untitled) (Baghdad Science Journal, 2022)
Today, the role of cloud computing in our day-to-day lives is very prominent. The cloud computing paradigm makes it possible to provide demand-based resources. Cloud computing has changed the way that organizations manage resources due to their robustness, low cost, and pervasive nature. Data security is usually realized using different methods such as encryption. However, the privacy of data is another important challenge that should be considered when transporting, storing, and analyzing data in the public cloud. In this paper, a new method is proposed to track malicious users who use their private key to decrypt data in a system, share it with others and cause system information leakage. Security policies are also considered to be integrated with the texts encrypted to ensure system safety and to prevent the violation of data owners ’ privacy. For this purpose, before sending the data to the cloud, it must be encrypted in such a way that operations such as max, min, etc. can be performed on it. The proposed method uses order-preserving symmetric encryption (OPES), which does not require decryption or re-encryption for mathematical operations. This process leads to a great improvement in delay. The OPES scheme allows comparison operations to be performed directly on encrypted data without decryption operands. According to the results, it is obvious that the proposed strategy is in a better position compared to the base paper in terms of the system’s ability to find the malicious elements that cause the problem of leakage and in terms of system security to prevent the violation of privacy.